Internationalisation of Education and Returns in the Labour Market - Jacques Poot; Matthew Roskruge (Institute for the Study of Labor (IZA), 2013)
The education services provided in any given country increasingly contribute to human capital that is employed in another country. On the one hand, graduates may seek to obtain the highest return to the knowledge they gained in their home country by working abroad. On the other hand, some students purchase educational services abroad and will subsequently work abroad, or return home to utilize the internationally acquired knowledge in the domestic labour market. In this paper we use data from the 2006-07 Adult Literacy and Life Skills survey in New Zealand to examine how years of foreign and domestic education affect earnings in the labour market. We account for differences in innate ability by aggregating subjective responses to pertinent questions in the survey and by incorporating parents' educational background. Our findings reconfirm the extensive evidence that education gained in a country of birth has generally a lower return in a foreign labour market than the native born receive in this labour market for the equivalent education. Post-settlement education in the host country has a higher return for migrants than for comparable native born. We also find that the highest returns are obtained among those who, after studying abroad, return home to work a fact for which there has been to date scarce evidence. Thus, exposure to foreign education can lead to a triple gain: for the country where the education is obtained, for the students' home country and for the students themselves.
Keywords: F22; I24; J24; J31; 330; international education; human capital; earnings; selection effects